2021
DOI: 10.3390/agronomy11102070
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Calciprill and Sodium Silicate Improves Chemical Properties of Low-pH Soil

Abstract: The highly weathered, acidic tropical soils are generally less fertile because of their low pH, high exchangeable acidity, and Al, Fe, and Mn saturations. Using soil amendments to solve the aforementioned problems is essential. To this end, Calciprill and sodium silicate are worth considering because of their high neutralizing value and dissolution to suppress exchangeable acidity and Al, Fe, and Mn hydrolysis, while at the same time increasing soil pH to improve the availability of inorganic N, available P, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…The significant suppression of exchangeable Al was due to the significant increase in soil pH, which transforms exchangeable Al into insoluble Al hydroxides through a precipitation reaction with OH ions [8,23,49]. The results of this study are similar to the findings of Ng et al [50] and Ng et al [51], who reported that the combined use of calcium-and silicon-based amendments can effectively suppress exchangeable Al in the soil by impeding Al hydrolysis over 120 days of incubation. This was due to their neutralizing ability, which can increase pH through the release of exchangeable Ca 2+ and SiO 4 4− concentrations.…”
Section: Effects Of the Application Of Calcium Silicate On Exchangeab...supporting
confidence: 83%
“…The significant suppression of exchangeable Al was due to the significant increase in soil pH, which transforms exchangeable Al into insoluble Al hydroxides through a precipitation reaction with OH ions [8,23,49]. The results of this study are similar to the findings of Ng et al [50] and Ng et al [51], who reported that the combined use of calcium-and silicon-based amendments can effectively suppress exchangeable Al in the soil by impeding Al hydrolysis over 120 days of incubation. This was due to their neutralizing ability, which can increase pH through the release of exchangeable Ca 2+ and SiO 4 4− concentrations.…”
Section: Effects Of the Application Of Calcium Silicate On Exchangeab...supporting
confidence: 83%